Feasibility and Safety of Flow Diversion in the Treatment of Intracranial Aneurysms via Transradial Approach: A Single-Arm Meta-Analysis - Liu, Xiang; Luo, Wenzhang; Wang, Mingyan; Huang, Changren; Bao, Kunyang (Frontiers in Neurology, 2022)
Abstract Background: While studies have confirmed that flow diversion(FD) can treat intracranial aneurysms via transradial approach(TRA), it remains unclear whether their treatment ultimately impacts safety and feasibility. We aim to conduct a systematic review and meta-analysis assessing the safety and feasibility after FD treatment of intracranial aneurysms via TRA. Methods: PubMed, EMBASE, and Web of Science were systematically reviewed. The primary outcomes were the success rate and the access-related complications of deploying FD via TRA. Meta-analysis was performed using a random or fixed effect model based on heterogeneity. And the publication bias was evaluated using a funnel plot. This study was registered with PROSPERO, number CRD42021244448. Results: Data from 8 studies met inclusion criteria (250 nonduplicated patients). The success rate was 93% (95%CI 0.86-0.98; I2 = 61.05%; P = 0.01). The access-related complications rate was 1% (95%CI 0-0.03; I2 = 0.00%; P < 0.01). The mainly access-related complications included radial artery spasm (85.7%) and radial artery occlusion (14.3%). And the TRA convert to transfemoral approach (TFA) was 7% (95%CI 0.02-0.14; I2 = 61.05%; P = 0.01). Conclusions: Although TFA is still the main access for FD in the treatment of intracranial aneurysms, the TRA also has a higher success rate and lower access-related complications rate. With the improvement of future experience and equipment, the TRA may become the main access for FD which has more advantages. Future studies should design prospective, multicenter randomized controlled studies for long-term follow-up.